INSTRUCTIONAL STRATEGIES FOR DIVERSE CLASSROOMS: A PEDAGOGICAL PERSPECTIVE - Dimitruk Elena (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2025)
The increasing diversity within today’s classrooms presents both significant opportunities and challenges for educators. Students now bring with them a wide range of cultural backgrounds, languages, learning abilities, socio-economic statuses, and personal experiences. This article explores effective instructional strategies that educators can implement to support inclusive, equitable, and responsive teaching in such diverse learning environments. Drawing from a broad review of educational theory and literature, the study identifies key pedagogical approaches including differentiated instruction, universal design for learning (UDL), culturally responsive teaching, cooperative learning, scaffolding, and the integration of educational technology. Through a qualitative descriptive analysis, this article examines how these strategies align with inclusive education principles and how they can be practically applied across varied educational contexts. The findings emphasize that successful teaching in diverse classrooms requires flexibility, cultural competence, and a commitment to continuous professional growth. Ultimately, this article advocates for a pedagogical shift that not only addresses academic needs but also fosters equity, identity affirmation, and holistic student development.